Positioning of Russia in the World Ranking Competitiveness of Travel and Tourism - Klimova, Tatyana B.; Slinkova, Olga K.; Bogomazova, Irina V.; Vishnevskaya, Ekaterina V.; Yakovenko, Oksana V. (Journal of History Culture and Art Research, 2018)
This article analyzes positions of Russia in world tourist space on the basis of the tourism and travel competitiveness rating provided by the World Economic Forum. At the heart of rating lies The Travel and Tourism Competitiveness Index (TTCI) calculated on the basis of fourteen indicators grouped in four subindexes. On the basis of estimates of the indicators creating the index both the positive and negative influencing factors are allocated for a position of Russia in rating and The Travel and Tourism Competitiveness Index. It is noted that despite ambiguity of the estimates provided by the World Economic Forum, only complex assessment of the Russian tourism tendencies will allow defining new trends in its development and new mechanisms of increase in competitiveness of Russia in global tourist space.